Could the minor autohemotherapy be a complementary therapy for healthcare professionals to prevent COVID-19 infection? - Orscelik, Aydan; Karaaslan, Burak; Agiragac, Betul; Solmaz, Ilker; Parpucu, Murat (Annals of Medical Research, 2021)
Aim: Coronavirus disease (COVID-19) poses a public health threat to the whole world and healthcare professionals also had difficulties in protecting themselves. Ozone therapy is an alternative and complementary treatment method that is theoretically accepted as an inactivated and immunogenic vaccine. We aimed to evaluate the effectiveness of minor autohemotherapy in the COVID-19 pandemic on protection and anxiety in healthcare professionals. Materials and Methods: The minor autohemotherapy was performed on the healthcare professionals’ weekly/six times. A general questionnaire, the Worry and Anxiety questionnaire, and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) were used at the beginning and after 6 weeks from the beginning. Results: The study was started with 89 healthcare professionals and finished with 73 in total. The IPAQ- SF score was 718.11 ± 507.49 (median 583, low) before treatment, and decreased to 462.67 ± 250.65 (median 437, low) after treatment. The WAQ score was 34.79 ± 13.27 (median 36) before treatment and decreased to 22.19 ± 11.22 (median 21) after treatment. The median of the pre-treatment scores for both scales was statistically different from the median of the post-treatment scores (p <0.001). Conclusion: None of the healthcare professionals who performed the minor autohemotherapy had become sick or had COVID-19 positive test results. The results of our study reveal that healthcare professionals who were applied minor autohemotherapy worry and anxiety decreased despite decreasing physical activity levels of individuals.